CHRONIC PERIODONTITIS IN PATIENT WITH TYPE II DIABETES MELLITUS: A CASE REPORT - Inneke Cahyani; Anindita Laksitasari; Rahma Isnani Surya Asri (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
Chronic periodontitis is a periodontal disease that leads to alveolar bone destruction. Periodontitis with symptoms of tooth mobility can be experienced in patients with type 2 diabetes mellitus. This condition requires proper management from early detection of the disease to prevent its severity. A 62 year old female patient came to RSGMP Unsoed complained of tooth mobility and uncomfortable chewing. Clinical examination revealed several teeth mobility in grades 1 to 2. The patient had a history of type 2 diabetes mellitus several years ago. The second visit was scaling and root planing when the blood sugar was 170 mg/dl. Inflammatory condition of type 2 diabetes mellitus patients affects microvascular and macrovascular complications which can increase the severity of periodontitis to loss of alveolar bone attachment and cause tooth mobility.Chronic periodontitis and diabetes mellitus can mutually influence disease severity so the recommended treatments are regular glycemic monitoring and periodontal treatment in the form of scaling and root planning Keywords: Chronic periodontitis, diabetes mellitus, scaling and root planing, non-surgical periodontal therapy